1999
DOI: 10.1006/viro.1999.9921
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long Terminal Repeat Sequence Variation on Equine Infectious Anemia Virus Replication in Vitro and in Vivo

Abstract: The long terminal repeat (LTR) is reported to be one of the most variable portions of the equine infectious anemia virus (EIAV) genome. To date, however, no information is available on the effects of observed sequence variations on viral replication properties, despite a widespread assumption of the biological importance of EIAV LTR variation. EIAV LTR sequence variability is confined mostly to a small portion of the enhancer within the U3 segment of the LTR. Analysis of published EIAV LTR sequences revealed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…In vivo analysis of the proviral challenge strains by experimental infections of equids confirmed characteristic EIAV pathogenesis and virulence properties. Standard viral replication kinetics, including the induction of acute disease and progression to chronic disease, were observed for all three strains (19,32,34). Interestingly, assays of antibody responses elicited by experimental infections with variant challenge viruses indicated distinct neutralization phenotypes for the individual variant envelopes; each variant challenge virus was neutralized by immune serum from homologous virus infections, but not from heterologous virus infections (SI Fig.…”
Section: Development Of Variant Challenge Strainsmentioning
confidence: 94%
“…In vivo analysis of the proviral challenge strains by experimental infections of equids confirmed characteristic EIAV pathogenesis and virulence properties. Standard viral replication kinetics, including the induction of acute disease and progression to chronic disease, were observed for all three strains (19,32,34). Interestingly, assays of antibody responses elicited by experimental infections with variant challenge viruses indicated distinct neutralization phenotypes for the individual variant envelopes; each variant challenge virus was neutralized by immune serum from homologous virus infections, but not from heterologous virus infections (SI Fig.…”
Section: Development Of Variant Challenge Strainsmentioning
confidence: 94%
“…For example, the MA-1 variant of EIAV wyoming was selected by in vitro adaptation in equine dermal cells [14]. LTR variants have been shown to be rapidly eliminated in vivo [29,91]. LTR variations are associated with in vitro adaptation to nonnatural target cells such as non-equine cells or fibroblasts; in vivo replication probably requires a rapid adaptation of the LTR.…”
Section: Viral Evolution In Infected Animalsmentioning
confidence: 99%
“…Previous studies have retrospectively identified alterations in EIAV LTR enhancer sequences that are associated with longterm passage in macrophages or leukocyte cultures (56) or fibroblasts (6,25,27,43). These changes include loss and gain of transcription factor binding motifs (36).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have identified extensive EIAV LTR enhancer changes including multiple nucleotide insertions or deletions (27,57), whereas other studies have found more modest changes (6,43). LTR alterations that are associated with fibroblast tropism have been correlated with the alteration of LTR activity in a cellspecific manner (43,57); however, other reports suggest that the LTR changes found in tissue culture-derived isolates are not associated with cell-specific activity in vitro (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation